The Role of BJB University Bandung in Building a Learning Organization to Support the Development of Bank BJB Employee Competence: Peran BJB University Bandung dalam Membangun Learning Organization untuk Mendukung Pengembangan Kompetensi Karyawan Bank BJB - Siti Nabilah; Revi Anggraeni; Ivanda Febrianti; Mochamad Rizal Yulianto (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Human resource development in the banking sector requires continuous capability building to adapt to technological changes and competition. Specific Background BJB University serves as an internal corporate university designed to align employee competency development with organizational objectives at Bank BJB. Knowledge Gap However, empirical documentation detailing how corporate universities structure learning organizations in regional banking contexts remains limited. Aims This study analyzes the role of BJB University in establishing a learning organization and enhancing employee competence. Results The findings show that structured competency-based training, leadership programs, coaching, and digital learning platforms foster continuous learning and collaborative innovation. Novelty This paper provides an integrative framework linking corporate university operations with the people, process, and physical evidence dimensions in regional banking. Implications Practically, these results offer strategic guidance for banking institutions to optimize talent retention and organizational agility through structured internal learning ecosystems. Keywords: BJB University, Corporate University, Learning Organization, Competency Development, Human Resources Key Findings Highlights BJB University aligns employee competency development directly with corporate business strategies. Continuous learning is fostered through structured digital learning platforms, leadership development, and mentoring. Organizational capability enhancement depends on the integration of people, process, and physical evidence infrastructure.